Provably secure robust optimistic fair exchange of distributed signatures - WANG, Yujue (Institutional Knowledge at Singapore Management University, 2016)
We introduce the concept of optimistic fair exchange of distributed signatures (OFEDS) which allows two groups of parties to fairly exchange digital signatures. Specifically, an authorized set of parties from each group can jointly take part in the protocol on behalf of the affiliated group to fulfill obligation, and a semi-trusted arbitrator will intervene in the protocol only when there are disputes between two sides. Our OFEDS extends the functionality of optimistic fair exchange of threshold signatures to a more generic case. We formalize the security model of OFEDS, in which besides the standard security requirements for existing optimistic fair exchange protocols, robustness is incorporated so that OFEDS can be successfully performed even when there exist some dishonest signers. We propose a non-interactive construction of OFEDS based on the well-established Computational Diffie-Hellman (CDH) assumption. Our proposal shows that there exists CDH-based OFEDS for any general monotone access structure. Theoretical and experimental analyses demonstrate our OFEDS construction has reasonable efficiency for real applications.